Theoretical experimental aspects of composition with polymeric matrix reinforced with polymer particles - Indrit Vozga; Vladimir Kasemi (Zaštita Materijala)
The development of composite materials and related design and production methods is one of the most important advances in the history of materials. They can be accurately modeled to respond to the requirements of the most specific applications. Many composites show, in addition to high mechanical properties, also high resistance to corrosion at high temperatures, to oxidation and wear. These unique features give design possibilities that are not achieved with any of the traditional monolithic materials. Many technological processes of composites are best suited for the production of large and complex structures, which has allowed their compaction and realization in the form of "one body", thus reducing production costs. The case of the composite with polymeric matrix reinforced with polymer particles is also interesting. PS and HDPE are two of the most used plastics in the world with a production scale of billions of tons. Less than 10% of this production is recycled. One use for recycled plastics, especially HDPE, is to melt into profiles that resemble beams, hence the term plastic beams. These products are used as building materials in many applications. One drawback of some plastic beam products is their tendency to slip.